Effect of Oral Administration of Emtricitabine on Woodchuck Hepatitis Virus Replication in Chronically Infected Woodchucks - Korba, Brent E. (American Society for Microbiology, 2000)
Emtricitabine [(−)FTC] [(−)-β-2′,3′-dideoxy-5-fluoro-3′-thiacytidine] has been shown to be an effective inhibitor of hepatitis B virus (HBV) in cell culture, with a potency and selectivity that are essentially identical to those of lamivudine. The antiviral activity of oral administration of (−)FTC against WHV replication in chronically infected woodchucks, an established and predictive model for antiviral therapy against HBV, was examined in a placebo-controlled study. (−)FTC significantly reduced viremia and intrahepatic WHV replication in a dose-dependent manner that was comparable to the antiviral activity of lamivudine observed in previous studies conducted by our laboratories. No effect on the levels of hepatic WHV RNA or the levels of woodchuck hepatitis surface antigen or anti-woodchuck hepatitis surface and core antibodies in the serum of the treated animals was observed. No evidence of drug-related toxicity was observed in any of the animals treated.